2019
DOI: 10.1177/0022034519843106
|View full text |Cite
|
Sign up to set email alerts
|

Increased Phosphatidylserine on Blood Cells in Oral Squamous Cell Carcinoma

et al.

Abstract: The specific function of phosphatidylserine (PS) in the context of the development of a hypercoagulable state among individuals with oral squamous cell carcinoma (OSCC) is uncertain. The goal of this study was therefore to assess the exposure of PS on microparticles (MPs) as well as on endothelial and blood cells and to assess procoagulant activity (PCA) as a function of the stage of OSCC progression. We recruited patients with OSCC ( n = 63) as well as healthy controls ( n = 26) to participate in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Interestingly, our data also showed no major effects on oral cancer cells following treatment with the PS-AuNP. Liu et al [ 48 ] recently reported increased PS in blood cells, microparticles, and serum-cultured endothelial cells in patients with oral squamous cell carcinoma (OSCC) compared to healthy controls. This could indicate that OSCC may use PS over-expression as an immunosuppressive strategy for tumor progression, especially for stage III/IV cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data also showed no major effects on oral cancer cells following treatment with the PS-AuNP. Liu et al [ 48 ] recently reported increased PS in blood cells, microparticles, and serum-cultured endothelial cells in patients with oral squamous cell carcinoma (OSCC) compared to healthy controls. This could indicate that OSCC may use PS over-expression as an immunosuppressive strategy for tumor progression, especially for stage III/IV cancers.…”
Section: Discussionmentioning
confidence: 99%
“…PtdSer has been detected in microparticles in blood that have been implicated in hypercoagulation in diabetic kidney disease (Yu et al, 2018), cancer (Lea et al, 2017; Liu et al, 2019; Zhao et al, 2016), and inflammation (Zhao et al, 2016). Whether PtdSer is also an integral component of lipoproteins in humans is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, FXa binds to FVa to form the prothrombinase complex, which is catalyzed by the PS-rich lipid membrane surface, leading to a burst of thrombin formation, which is required for rapid and local fibrin mesh formation. PS is involved in the amplification phase by binding two types of protein domains: γ-carboxyglutamate-rich (Gla) domains (prothrombin, FVII, FIX, and FX) and C-type lectin domains (FV and FVIII) ( Gilbert et al, 2015 ; Liu et al, 2019 ). Specifically, the assembly of the tenase (factors VIIIa, IXa) and prothrombinase (factors Va, Xa) complexes drive the coagulation cascade.…”
Section: Introductionmentioning
confidence: 99%